Penerapan Metode Regresi Linear Sederhana Untuk Prediksi Harga Beras di Kota Padang - Hasibuan, Lilis Harianti; Musthofa, Syarto (JOSTECH: Journal of Science and Technology, 2022)
The purpose of this research is to get predictions of rice prices. Linear regression is usedÂ  as a method of predicting rice prices in the next X(t) period. In this study, the actual rice price Y(t) is the effect variable and the time period is the causal variable. The linear regression equation obtained is Y'=13562.561+9.041958X. Testing the accuracy of the prediction results was carried out using RMSE with a value of 0.126. The prediction of rice prices using the linear regression method can be said to be in the very good category, it can be seen that the RMSE value is very small in the test and meets the standard.